Manajemen Program Unggulan Menuju Sekolah Bermutu di SMAIT Thariq Bin Ziyad Bekasi - Sri Widianti; Matin; Sugiarto Sutomo (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2023)
Quality educational results can be seen from the achievements achieved by students, both in academic and non-academic achievements. One of the parameters of a quality school is how schools are able to manage management functions both from planning, organizing, implementing and evaluating the school's superior programs that are their branding so that they can be trusted by the community in entrusting their sons and daughters. This research was conducted at the Integrated Islamic High School (SMAIT) Thariq Bin Ziyad Bekasi which implemented the school's flagship program dalam node Akhlak, Al Quran, Academic and Language (A3B), dimana. The research method uses descriptive qualitative with observation, interviews with informants and documentation studies. The data that has been obtained is reduced and then presented in the form of results and discussions. The results of this study found that the school's flagship program can have an impact on improving the quality of education and high public trust.